Outcome of Fast Track Surgery (FTS) or Enhanced Recovery after Surgery (ERAS) in Major Gynecological Surgeries - Sobia Nawaz, Naila Mushtaq, Sobia Nawaz, Naila Mushtaq (Journal of Rawalpindi Medical College, 2018)
Background: To determine the outcome of fast track in major gynecological surgeries in terms of frequency of tolerating early oral feeding and shorter hospital stay. Methods: In this descriptive study all patients undergoing major gynecological procedures under general anaesthesia, (total abdominal hysterectomy TAH, vaginal hysterectomy VH,Laparotomy for ectopic pregnancy or ovarian cyst) and without any co-morbid diseases were included. Patients in whom fast track method was applied i.e. patients were mobilized 8 hours after surgery and urinary catheter and i/v cannulas were removed if the patient was haemodynamically stable. Oral liquids were allowed 8 hours after surgery (early oral feeding) with rapid progression thereafter. Patients were observed if they are tolerating early oral feeding i.e. they were having nausea, vomiting, paralytic ileus or not and recorded. Patients were assessed if they were fulfilling the criteria and could be discharged on day 2 (short hospital stay). All patients were given intravenous ceftriaxone 1 g preoperatively. The patient who adequately mobilized without assistance, tolerated early oral feeding and pain free were discharged. Results: Out of 150 cases of fast track surgery, we recorded mean duration of stay at hospital as 2.81+1.20 days. Frequency of shorter hospital stay was recorded in 38.67% and early oral feeding was recorded in 92.67% . Conclusion: The outcome of fast track in major gynecological surgeries in terms of frequency of tolerating early oral feeding and shorter hospital stay is better than traditional method.